(untitled) - Petruzella, Frank D. (Boston, 2005)
This unique supplement, available for the first time with Petruzella's Programmable Logic Controllers, 3rd Edition, allows students and working technicians to use powerful simulation software to model and modify PLC operations. The printed manual has exercises that parallel chapters in the text, with illustrations and step-by-step procedures for users to follow. The bound-in CD-ROM provides users a fully functional copy of PSIM, a student version of the LogixPro software, plus a collection of sample simulations and other background information. The manual can be used with either PSIM or the full version of LogixPro.
PLC
Keywords: Telecommunication systems,Công nghệ điều khiển tự động,Programmable controllers,Hệ thống viễn thông